Awareness levels of teachers of child negligence and abuse: Rural area example - Mehmet Emin Parlak; Mehmet Yavuz Ozbey (Medicine Science, 2022)
It was aimed to determine the frequency of teachers' encounters with child neglect and abuse and their views on this subject in this study. It is a cross-sectional and descriptive study. Three hundred eighty-eight teachers working in 40 primary schools and 18 high schools were selected with the cluster sampling method. Data was collected through a survey. The Chi-Square tests were applied. 21.6% of the research group reported that they encountered cases of neglect and 46.1% reported cases of abuse. 41.8% of the research group stated that they did not receive child neglect and abuse training. While 26.2% of them find themselves sufficient in diagnosing cases of neglect and abuse, 73.8% find themselves partially sufficient or insufficient. A significant relationship was found between self-efficacy in diagnosing cases according to gender, the number of years of work, receiving education about neglect and abuse, type of abuse, and reporting. While the rate of women who consider reporting suspected child neglect or abuse mandatory is significantly higher than men, the rate of those who find themselves sufficient in diagnosing child neglect or abuse is significantly higher in males. Among the abuse types, the rate of teachers who are faced with the suspicion of sexual abuse in diagnosing the case is significantly higher than the other types of abuse. The rate of teachers receiving training on cases of neglect and abuse and finding themselves competent in this regard is low. Men, those who have worked for 16-20 years, and teachers who have been trained in this subject find themselves more competent in diagnosing child neglect or abuse. Diagnosis the sexual abuse is higher than the other types. Regardless of the incident, the most important factor for teachers to find themselves competent is acquiring knowledge through pre-service or in-service training. [Med-Science 2022; 11(4.000): 1541-7]